Breast Brucellosis in Taif, Saudi Arabia: cluster of six cases with emphasis on FNA evaluation - Dalal Nemenqani; Nausheen Yaqoob; Hatem Khoja (Journal of Infection in Developing Countries)
Background: Brucellosis is an endemic zoonosis seen in a variety of geographical locations such as the Middle East and Latin American and Mediterranean countries. Brucellosis is hyper- endemic in Saudi Arabia with an incidence of 5.4 per 1000 per year. Breast involvement very rarely occurs as a focal complication of brucellosis. Methodology: We report six cases of breast brucellosis retrieved from the files of the patients. Fine needle aspiration (FNA) was performed on all patients. In all cases direct smears were made at the patient's side for assessment of sample quality. Cytospin and cell block preparation was done and Gram, periodic acid-Schiff and Ziel-Nelson stains were done on all samples. Microbiological analysis included routine fungal and bacterial culture for tuberculosis. Results: Age range was 20 to 48 years with a median of 22 years. Two patients gave history of raw milk ingestion, one was lactating, and one patient was pregnant. Cytomorphologic features of brucellosis in the breast include an abscess-like background with granulomatous inflammation. Cytology of the patients presented with breast abscess showed predominant neutrophilic infiltrate compatible with acute pyogenic inflammation. Culture was positive for B. melitensis in all cases. Conclusion: Brucellosis should be kept in mind in the differential diagnosis of breast abscess in endemic areas where ingestion of unpasteurized milk and milk products is common. Needle aspiration establishes a preliminary diagnosis and has the advantage of material submission for microbiologic cultures and provides focal treatment along with long-term combined antibacterial treatment for the control of systemic infection.